The Superior Geotraverse Project - Goodwin, A.; West, G. (Geoscience Canada, 1974)
Summary The Superior Geotraverse Project is a cooperative geological and geophysical research program being carried out by the Precambrian Research Group of the University of Toronto, assisted by scientists from other universities. The purpose of the project is to study the origin of the Archean crust north of Lake Superior in a 300 mile long, N-S corridor which crosses three volcanic-plutonic belts (Uchi, Wabigoon and Shebandowan) and two metasedimentary-gneiss belts (English River and Quetico). Six different models for the origin of the Archean crust are under consideration: no decision between competing models will be possible until further work is done. One possible model, however, is that the crust developed in three stages: 1 ) development of Archean "oceanic" crust, 2) development of Archean "island arc" crust as a result of subduction, 3) accumulation of greywackes in foreland basins.